Strawberry Hill, The Seat of Countess Dowager Waldegrave, Middlesex - Neale, J.P.; Radclyffe, William (Tufts Archival Research Center, 2008)
This illustration is from Charles Knight's,"London," Vol. 3. This image was inserted by Edwin C. Bolles and is not found in the original.